Pengaruh Faktor Sosial Ekonomi Dan Pendidikan Orang Tua Terhadap Eksploitasi Anak Di Dunia Kerja Sebagai Pelanggaran Hak Asasi Manusia - Denies Salwani; Laura Shafa; Syafariah (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Child exploitation is an activity carried out for personal or family interests. The prohibition on child exploitation is regulated in Law No. 35 of 2014 concerning child protection, but currently child exploitation still often occurs due to economic factors and low levels of education. Children are forced to work in heavy work that is not appropriate for their age due to insufficient economic demands. Low levels of education also influence child exploitation, parents who do not have further education will help in getting decent work. This study uses a normative juridical method with a statutory approach to spread the application of the law and find solutions to the problem. The results of this study indicate that economic factors and low levels of education in Indonesia cause the continued prevalence of child exploitation. Therefore, the role of the Government, Non-Governmental Organizations, and the surrounding community is needed to help prevent child exploitation by raising awareness of children's rights and strengthening law enforcement. With these steps, it is hoped that child protection from exploitation can be realized.